Can bioelectrical impedance analysis be used to identify water loading in patients with anorexia nervosa?– Implications from experimental measurements in young, healthy, and normal weight women - Nadja Knoll-Pientka; Dorina Schils; Katrin Pasternak; Sandra Czarnetzky; Christoph Jansen; Gertraud Gradl-Dietsch; Jochen Seitz; Eva-Maria Skoda; Lars Libuda; Adam Schweda; Martin Teufel (Journal of Eating Disorders)
Abstract Anorexia nervosa (AN) is a severe mental disorder, and patients with AN are characterized by a low body weight and a fear of gaining weight. Restoration of body weight to the normal range is one major treatment aim, which can be a challenging process for the patients. Hence, as a psychopathological symptom of AN, weight manipulations such as water loading before weighing are commonly observed in clinical routine. Biological impedance analysis (BIA) is a helpful tool in routinely visualizing changes in body composition during the refeeding process. Here, we targeted the question whether BIA could potentially detect water loading in healthy, young and normal weight women serving as a preclinical model for patients with AN. Sixty-one women (mean ± SD, 22.2 ± 2.2 years, 20.4 ± 1.0 kg/m2) were included in the analyses. We used a full experimental setting with a cross-over design on two consecutive days. On both days, all participants underwent a baseline BIA in the fasting state (t0). Directly thereafter, participants either consumed 1000 ml of tap water (intervention-condition) or waited for the second BIA measurement 20 min (t1) after baseline (control-condition), and vice versa the subsequent day. Two further BIA measurements took place at 40 (t2) and 60 min (t3) after baseline. After water consumption, we found increases in derived fat mass (FM) and phase angle at t1 to t3, decreases at t1 and subsequent increases at t2 and t3 in extracellular water (ECW) and total body water (TBW). In contrast, skeletal muscle mass (SMM) and ECW/TBW remained rather stable. In the control-condition, most parameters remained constant. Our study provided insight into the changes of impedance raw data and derived body compartments after water consumption among young, healthy and normal weight women. Although the considerable increase of FM in combination with a rather stable course of SMM, as found in our experiment after the consumption of water, could be a potential hint for water loading, further investigation considering the limitations of the present study as for instance the different metabolisms of patients with AN vs. healthy women is required, before transferability to the clinical setting will be given.